Reclaiming sovereignty: Decolonizing wetland governance in Bangladesh for sustainable futures - Mohammad Fakhrus Salam; Habibur Rahman Masrur (Green Governance: Exploring Politics, Social Justice, and the Environment, 2026)
Background: Wetlands in Bangladesh, such as haors and beels, are living, dynamic landscapes that sustain biodiversity, livelihoods, and culture across generations. Yet, governance models rooted in colonial resource extraction and bureaucratic control persist, marginalizing these vital socio-ecological systems. Post-independence state-led development continues to prioritize technical solutions over community knowledge and ecological resilience. This has created a crisis in regions like the haors, where institutional incoherence meets acute ecological vulnerability. Methods: This study employs a qualitative interpretive design grounded in socio-ecological and historical perspectives to examine wetland governance in Bangladesh’s haor region, drawing on extensive secondary sources and using iterative thematic analysis informed by a decolonial framework to explore power dynamics, community experiences, and postcolonial institutional legacies. Findings: Informed by decolonial theory, political ecology, and Indigenous knowledge, this paper argues for a radical paradigm shift. Through fieldwork and community narratives, it highlights the urgent need to move beyond centralized, reactive governance. Instead, it calls for institutional decolonization centering local leadership, plural knowledge systems, and justice in environmental decision-making. Securing the future of Bangladesh’s wetlands demands not just technical innovation, but historical reckoning and epistemic justice, restoring governance to those whose lives are woven into these landscapes. Conclusion: Wetland governance in Bangladesh requires a decolonized, justice-oriented shift that centers community authority, participatory institutions, and the integration of local and scientific knowledge to ensure ecological resilience and social equity. Novelty/Originality of this article: This study applies a decolonial political ecology lens to wetland governance in Bangladesh, proposing a justice-oriented, community-centered model to replace centralized postcolonial control and strengthen socio-ecological resilience.